Perinatal Mental Health Disorders in Indonesia: A Systematic Review of QuantitativeStudies (2015–2024) - Putri, Noviyati Rahardjo; Rahmah, Ulinuha Aufa; Perestroika, Grhasta Dian (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2025)
Perinatal mental health disorders, especially depression and anxiety, are prevalent among women in low- and middle-income countries (LMICs), including Indonesia. These conditions can affect both maternal well-being and child development. This systematic review aimed to identify and synthesize key risk factors associated with perinatal mental health disorders among women in Indonesia. A systematic search was conducted in PubMed, Scopus, and Google Scholar for quantitative studies published between 2015 and 2024. Inclusion criteria included studies involving pregnant or postpartum women in Indonesia, using quantitative designs, and reporting on risk factors for depression and/or anxiety. The review followed PRISMA 2020 guidelines. Data extraction and screening were conducted manually by reviewers. Out of 434 identified records, six studies met inclusion criteria. Most employed cross-sectional designs and focused on sociodemographic, psychosocial, obstetric, and psychological factors. Common risk factors included young maternal age, low education, unstable employment, lack of social support, and history of mental illness. Several studies also identified low mental health literacy and poor maternal-fetal attachment as contributing factors. The included studies were mostly cross-sectional, limiting causal inference. This review highlights the need for routine mental health screening, greater provider training, and community-based interventions in maternal health care. Future research should prioritize longitudinal designs and assess the effectiveness of policy implementation.